Exploring Jason Reynolds's Long Way Down as Young Adult Literature: A Genre Criticism - Sugianto, Clarissa Nathania; Pramesti, Tri (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research explores the classification of Jason Reynolds’s Long Way Down as Young Adult literature through the lens of genre criticism, focusing on its narrative structure, adolescent voice, and thematic depth. Utilizing theoretical frameworks by Nilsen and Donelson as well as Mertz and England, the research identifies core characteristics of Young Adult literature such as youthful perspective, rapid plot progression, and engagement with real-world issues, embedded within Reynolds’s verse narrative. This research employs a qualitative descriptive approach through close reading and textual analysis, examining Will Holloman’s internal struggle during a 60-second elevator ride that symbolically descends into questions of identity, grief, revenge, and the moral consequences of violence. Set within a marginalized urban environment, the novel portrays how systemic racism, toxic masculinity, and constrained agency impact adolescent development. Structural and stylistic elements, such as the free-verse format, fragmented cadence, staccato lines, and ghostly encounters, are analyzed to reveal how the novel both aligns with and challenges Young Adult literary conventions. The findings suggest that Long Way Down not only fulfills the essential traits of Young Adult literature but also expands the genre’s boundaries through its poetic form and layered social critique. By integrating genre theory and literary analysis, the study highlights how Reynolds’s narrative reflects a complex portrayal of adolescence shaped by cultural and communal expectations. Ultimately, Long Way Down exemplifies the evolving nature of Young Adult literature, bridging poetic experimentation with urgent, socially grounded storytelling and affirms its relevance as a genre that speaks directly to the emotional and ethical dilemmas faced by today’s youth.